Potential Factors Predicting Histopathologically Upgrade Discrepancies between Endoscopic Forceps Biopsy of the Colorectal Low-Grade Intraepithelial Neoplasia and Endoscopic Resection Specimens. (6th June 2022) - Hong, Junbo; Wang, Yining; Deng, Jiangshan; Qi, Miao; Zuo, Wei; Hao, Yuanzheng; Wang, Anjiang; Tu, Yi; Xu, Shan; Zhou, Xiaodong; Zhou, Xiaojiang; Li, Guohua; et al.
Abstract : Background . It was gradually accepted that endoscopic fragment biopsy (EFB) diagnosis cannot accurately guarantee the absence of higher-grade neoplasms within the lesion of the digestive tract. There are no well-established predictors for histopathologically upgrade discrepancies between EFB diagnosing colorectal low-grade intraepithelial neoplasia (LGIN) and endoscopic resection (ER) specimens. Methods . A total of 918 colorectal LGINs was histopathologically diagnosed by EFB, including 162 cases with upgrade discrepancy and 756 concordant cases. We compared clinicopathological data of EFB and ER specimens between these two groups. Multivariate analysis was performed to identify predictors for this upgrade histopathology. Results . The predominant upgrade discrepancy of LGINs diagnosed by EFB was upgrades to high-grade dysplasia (114/918, 12.4%), followed by upgrades to intramucosal carcinoma (33/918, 3.6%), submucosal adenocarcinoma (10/918, 1.1%), and advanced adenocarcinoma (5/918, 0.5%). NSAID history (OR 4.83; 95% CI, 2.27-10.27; p < 0.001 ), insufficient EFB number (OR 2.99; 95% CI, 1.91-4.68; p < 0.001 ), maximum diameter ≥ 1.0  cm (OR 6.18; 95% CI, 1.32-28.99; p = 0.021 ), lobulated shape (OR 2.68; 95% CI, 1.65-4.36; p < 0.001 ), erythema (OR 2.42; 95% CI, 1.50-3.91; p < 0.001 ), erosion (OR 7.12; 95% CI, 3.91-12.94; p < 0.001 ), surface unevenness (OR 2.31; 95% CI, 1.33-4.01; p = 0.003 ), and distal location of the target adenoma (OR 3.29; 95% CI, 1.68-6.41; p < 0.001 ) were associated with the histologically upgrade discrepancies. Conclusion . NSAID history, insufficient EFB number, adenoma size and location, and abnormal macroscopic patterns are potential predictors for upgrade histopathology of LGINs diagnosed by EFBs. The standardization of EFB number and advanced imaging techniques could minimize the risk of neglecting the potential of this upgrade histopathology.